FACTORS AFFECTING STOCK PRICES OF INFORMATION AND COMMUNICATION TECHNOLOGY SECTOR IN THE STOCK EXCHANGE OF THAILAND - Vongsuwanlert, Warinda; Pongsupatt, Apichat (Journal of Buddhist Education and Research (JBER), 2023)
The purpose of this study was to explore the factors affecting stock prices of Information and Communication Technology sector in the Stock Exchange of Thailand (SET). In this study the secondary data of 26 companies listed on Information and Communication Technology sector in the Stock Exchange of Thailand was collected covering the period from 2018 to 2021, entirely the 4 years. This study examined 6 independent variables including Book Value per Share (BVPS), Return on Assets (ROA), Earning per Share Growth Rate (GR), Debt to Assets Ratio (DA), Dividend Yield (DY) and Free Cash Flow (FCF). This data was analyzed by the Panel Least Squares Method, Fixed Effect Regression Model (FEM). The results showed that factors affecting stock prices of Information and Communication Technology sector in the Stock Exchange of Thailand with positively statistical significance level of 0.05 was Book Value per Share (BVPS), Return on Assets (ROA) and Debt to Assets Ratio (DA) with an R-Square of 0.9441.